Gyrokinetic simulation of the interplay between ion temperature gradient turbulence and reversed shear Alfvén Eigenmodes - Yuheng Yang; Lei Ye; Yang Chen; Nong Xiang; Youwen Sun (Nuclear Fusion)
A nonlinear gyrokinetic simulation, which incorporates both the reversed shear Alfvén eigenmode (RSAE) and the ion temperature gradient (ITG) turbulence, has been performed using the electromagnetic gyrokinetic Particle-In-Cell (PIC) code GEM. Strong nonlinear wave coupling and energy transfer between RSAE and ITG turbulence have been observed. Specific analyses show that the n  = 4 Alfvén eigenmode primarily interacts with the ITG harmonics with long wavelength ( $n\unicode{x2A7D} 16$ ). It is found that a background ITG turbulence can suppress the saturation level of RSAE and change the energetic particle transport. The frequency up-shift of RSAE and the frequency modulation on ITG components by RSAE are also observed. The impacts of the initial condition on the RSAE-ITG turbulence simulation are also discussed.